Relação de propriedades mecânicas do complexo articular domediopé com a medida clínica do alinhamento antepé-perna - Bruno Dayrell da Costa Paes (2018)
The clinical measure of forefoot-shank alignment (FSA) predicts the amount of footpronation during weight-bearing tasks, which may be related to lower limb injuries. FSAmight reflect the mechanical resistance of the midfoot joint complex (MFJC) to forefootinversion, which is a component of weight-bearing foot pronation. This study investigated ifMFJC resistance to inversion is related to the FSA. Forty-six healthy individuals (27 males;19 females) with mean age of 26.4 years (SD 5.3) participated. In this study, FSA wasmeasured with photographs. The mechanical resistance of the MFJC to inversion wasmeasured using the Torsimeter, which is an equipment with a torque meter designed toassess midfoot resistance torque and stiffness. Correlation coefficients were calculatedbetween each MFJC resistance variables and the FSA (=0.05). Multiple linearregressions were performed to test whether MFJC resistance variables collectively explainFSA). There were significant moderate correlations of FSA with maximum absolute torque(r=-0.334, p=0.023), maximum absolute stiffnes (r=-0.314, p=0.007) and resting position(r=0.395, p=0.007). Regression models showed that combined MFJC resistance variablessignificantly and moderately explained FSA values (0.189r20.202; 0.008p0.011). Inthe regression models, only resting position significantly explained FSA. Therefore, theMFJC variables did not show complementary contributions to the explanation of FSA. Themechanical resistance of the MFJC to forefoot inversion is associated to FSA: the greaterthe resistance, the smaller the FSA. These results support the idea that the FSA measureis associated to weight-bearing foot pronation because it partially reflects the mechanicalresistance to forefoot inversion provided by the MFJC soft tissues.